2016
DOI: 10.1002/jgm.2890
|View full text |Cite
|
Sign up to set email alerts
|

CFHR2‐rs2986127 as a genetic protective marker for acute anterior uveitis in Chinese patients

Abstract: The present study reveals an association between CFHR2-rs2986127 and AAU diagnosis, especially with respect to gender, AS status and other clinical signs, such as posterior segment involvement. Our results may further enrich the growing understanding of uveitis genetics, and raise the clinical diagnostic accuracy of this disease. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Another key component is the complement system, which is also involved in innate immunity and inflammatory responses. Genetic associations of complement factor H (CFH), complement factor B (CFB), complement factor I (CFI) and complement factor H related 2 (CFHR2) have been reported [ 8 , 20 23 ]. Notably, CFB localizes to the MHC class III region.…”
Section: Acute Anterior Uveitismentioning
confidence: 99%
“…Another key component is the complement system, which is also involved in innate immunity and inflammatory responses. Genetic associations of complement factor H (CFH), complement factor B (CFB), complement factor I (CFI) and complement factor H related 2 (CFHR2) have been reported [ 8 , 20 23 ]. Notably, CFB localizes to the MHC class III region.…”
Section: Acute Anterior Uveitismentioning
confidence: 99%
“…We detected that the serum levels of immunoglobulins, including complement factor H, complement component C8 alpha chain, complement factor I, complement factor H-related protein 3 (Fragment), complement component C6, complement factor B, complement C5, and properdin were lower in LA and MA buffalo than in HA buffalo ( Table 1 ). Complement factor H is a member of the complement regulator and plays an important role in complement activation pathways [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Studies have shown that CFHR2 is important in the gender difference in the incidence of acute anterior uveitis. 33 In addition, it has a wide range of applications in terms of resistance to pathogen invasion and pulmonary arterial hypertension associated with congenital heart disease. 34 However, there have been no studies investigating the roles of CFHR1 and CFHR2 in tuberculosis, especially osteoarticular tuberculosis.…”
Section: Discussionmentioning
confidence: 99%